2009
DOI: 10.1183/09031936.00140508
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary changes induced by trans,trans-2,4-decadienal, a component of cooking oil fumes

Abstract: Cooking oil fumes (COF) are known to be associated with respiratory diseases and risk of lung cancer. Involvement of trans,trans-2,4-decadienal (tt-DDE), a major component in COF, is suspected.Male CD-11 (ICR) mice were intratracheally instilled with either 8 or 24 mg?kg -1 tt-DDE weekly for 8 weeks. Total numbers and types of cells in bronchoalveolar lavage fluid (BALF), as well as pathological changes, and inflammatory gene modulations in the lung tissues were assessed. We demonstrated that the number of alv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Tissue microarray covering tissue sections of oral cavity carcinoma progression, OR802 (10 cancer adjacent tissues or normal tissues, 7 hyperplasia epithelia, 8 benign tumors, and 45 oral carcinoma) were purchased from US BIOMAX. Immunohistochemistry was performed as previously described [ 35 ]. Briefly, all paraffin sections were dewaxed and rehydration followed by heating in a 0.01 M citrate buffer for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…Tissue microarray covering tissue sections of oral cavity carcinoma progression, OR802 (10 cancer adjacent tissues or normal tissues, 7 hyperplasia epithelia, 8 benign tumors, and 45 oral carcinoma) were purchased from US BIOMAX. Immunohistochemistry was performed as previously described [ 35 ]. Briefly, all paraffin sections were dewaxed and rehydration followed by heating in a 0.01 M citrate buffer for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…This finding suggests that the adverse effect of fried meat intake may be most evident in later stages of lung carcinogenesis, although the relevant experiments have yet to be conducted in order to test a late-stage hypothesis. There is experimental evidence supporting a role for cooking-fume constituents, for which there is reasonable overlap with fried meat constituents (19,44), as promoters of lung cancer development by inducing proteins that are involved in regulating apoptosis and tumor angiogenesis (54,55). If the results from future experimental studies support a latestage model for the fried meat-lung cancer association, then our findings would carry important and encouraging prevention implications because a lower lung cancer risk could be realized within a relatively short time period following an individual's reduction in fried meat intake.…”
Section: Fried Meat Intake and Lung Adenocarcinoma Riskmentioning
confidence: 99%
“…Some volatilized oils, such as olive and peanut, are low in PAHs compared to others such as soybean or rapeseed 20 . Trans-2,4-decadienal (tt-DDE), found in cooking fumes, can induce cell proliferation and cytokine production from oxidative stress 2123 . Previous studies have suggested a dose-response relationship between lung cancer risk and years of cooking fumes exposure, particularly with high temperature frying which volatilizes cooking oils 24, 25 .…”
Section: Introductionmentioning
confidence: 99%
“…20 Trans-2,4-decadienal (tt-DDE), found in cooking fumes, can induce cell proliferation and cytokine production from oxidative stress. [21][22][23] Previous studies have suggested a dose-response relationship between lung cancer risk and years of cooking fumes exposure, particularly with high temperature frying which volatilizes cooking oils. 24,25 Chinese-style cooking often involves volatilization of oils, potentially exposing people to more fumes than cooking methods from other regions of the world.…”
mentioning
confidence: 99%